Designing of carbon fiber-reinforced polymer (CFRP) composites for a second-life in the aeronautic industry: strategies towards a more sustainable future - Borges, Carolina; Chícharo, A.; Araújo, A.; Silva, J.; Santos, R. M. (Frontiers in Materials, 2023)
In this work, carbon fiber-reinforced polymer (CFRP) composite “residues” were incorporated into a poly(etheretherketone) (PEEK) matrix, as a strategy towards a more sustainable future, aiming at developing novel compounds for the aeronautic industry. The influence of two different fiber sizes (< 600 and 600-1000 μm) on the neat PEEK properties was assessed through formulations developed using a co-rotating twin screw-extruder, under optimized processing conditions. Furthermore, the potential thermo-oxidative degradation, and the recycling feasibility of the neat PEEK and its compounds, were evaluated by submitting the materials to several thermo-mechanical cycles. The results showed that PEEK compounds were successfully prepared, and presented a good fiber distribution and absence of fiber agglomerates. A positive impact on the mechanical performance of PEEK was found by the incorporation of 3.3 wt. % of short carbon fibers (sCF) with larger sizes (600-1000 µm). The reprocessing of neat PEEK and its compounds for 15 consecutive cycles demonstrated its remarkable thermo-mechanical stability, without any sign of degradation or irreversible loss of properties. The fiber length and fiber length distribution of reprocessed compounds showed that major variations occurred after the first extrusion cycle, especially for larger sizes.